Meteor radar functionality on the PANSY radar - Hashimoto, Taishi; Nishimura, Koji; Tsutsumi, Masaki; Sato, Toru; Sato, Kaoru (2018)
The Ninth Symposium on Polar Science/Interdisciplinary sessions: [IW] Whole atmosphere, Thu. 6 Dec. / Entrance Hall (1st floor), National Institute of Polar Research conference object